Evaluation of non-modifiable factors associated with post-dural puncture headache following subarachnoid block utilising 26 G quincke spinal needle: Prospective, observational study - Chander Mohan Negi; Shyam Bhandari; Ravinder Kumar; Shelly Rana; Radhika Sharma; Nishita Kaushal (Wolters Kluwer Medknow Publications, 2023)
Background and Aims: Post-dural puncture headache (PDPH) is one of the complications of the subarachnoid block (SAB), and the incidence of PDPH is influenced by various factors related to either patients or the type of spinal needle used. This study observed the incidence and severity of PDPH in relation to non-modifiable factors in the patients scheduled for surgeries under SAB. Methods: The study enrolled 302 obstetric and non-obstetric patients, aged 20-60 years, American Society of Anesthesiologists (ASA) I/II having body mass index (BMI) 18.5-29.9 kg.m-2 scheduled for surgeries under SAB utilizing 26 G Quincke spinal needle. Primary outcome was the incidence of PDPH in obstetric and non-obstetric patients. The secondary outcomes included onset, severity of PDPH, and association of age, BMI, and gender to PDPH. Results: The total incidence of PDPH was 5.6%, eight (7%) patients in obstetric and nine (4.8%) patients in non-obstetric group (P = 0.597). The onset of PDPH was comparable in obstetric 17.25 ± 3.69 and non-obstetric patients 18.0 ± 6.02 h (P = 0.663). None of the patient had severe PDPH. The BMI of the patients was not associated with the incidence of PDPH. The female patients among non-obstetric group had higher incidence of PDPH (P = 0.0002). The six patients having PDPH in non-obstetric group belonged to age-group of 31-40 yrs as compared to two above 40 years (P = 0.0173). Conclusion: Obstetric population had comparable incidence of PDPH to non-obstetric population. In the subgroup analysis of non-obstetric patients, the higher incidence of PDPH was observed in the female and younger patients.